(untitled) (ModaPalavra e-periódico, 2008)
It describes the historical context in education of the Design it developed in Argentina, it emphasizes the relations between learning and market, as much in local context as global and carefully analyzes the challenges in the formation of a young design, either before the new and advanced historical conditions, as technological and the human beings. It still presents the structure of the courses offered for the Facultad de Diseño y Comunicación of la Universidad of Palermo and its proposal pedagogical politician.